2018
DOI: 10.1115/1.4041361
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Mixing Efficiencies of Liquid-to-Liquid Chemical Injection Manifolds for Aquatic Invasive Species Management

Abstract: Aquatic invasive species (AIS) have spread throughout the United States via major rivers and tributaries. Locks and dams positioned along affected waterways, specifically lock chambers, are being evaluated as potential management sites to prevent further expansion into new areas. Recent research has shown that infusion of chemicals (e.g., carbon dioxide) into water can block or kill several invasive organisms and could be a viable option at navigational structures such as lock chambers because chemical infusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Carbon dioxide could be infused at a low level to deter mobile native species from the area before a containment barrier is erected to isolate the treatment. Large-scale CO 2 infusion systems to deter invasive fish are in development (Zolper et al 2018) and could be modified for application at select sites. Under-the-ice application of CO 2 may be a feasible option for reducing dreissenid populations in a small water body and has USEPA registration for this use (US Environmental Protection Agency 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Carbon dioxide could be infused at a low level to deter mobile native species from the area before a containment barrier is erected to isolate the treatment. Large-scale CO 2 infusion systems to deter invasive fish are in development (Zolper et al 2018) and could be modified for application at select sites. Under-the-ice application of CO 2 may be a feasible option for reducing dreissenid populations in a small water body and has USEPA registration for this use (US Environmental Protection Agency 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Gas transfer efficiency was calculated for dry ice treatments before fish testing (Zolper et al., in press). Measured CO 2 concentrations ( C CO 2 ) in experimental ponds and known pond volume ( V H 2 O ) were used to approximate the mass of CO 2 (mCO2D) dissolved in water (equation ).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, tests in flowing water found that CO 2 applied at 75 mg/L reduced the distribution of fish and decreased the upstream movement of fish by approximately 50% (Cupp et al 2017a). Researchers are also developing methods to efficiently and consistently deliver chemicals like CO 2 into key management locations (Zolper et al 2018).…”
Section: Carbon Dioxidementioning
confidence: 99%
“…Researchers are also developing methods to efficiently and consistently deliver chemicals like CO 2 into key management locations (Zolper et al. 2018).…”
Section: New Control Technologiesmentioning
confidence: 99%